A slow swelling polymer microsphere and emulsion thereof, and a preparation method and application thereof

CN117624458BActive Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202210950536.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-09
Publication Date
2026-10-30
Estimated Expiration
2042-08-09

AI Technical Summary

Technical Problem

[0004]CN105368422A公开了一种预交联体膨颗粒调剖剂及其制备方法,所述的预交联体膨颗粒调剖剂合成原料2-丙烯酰胺基十八烷基磺酸或2-丙烯酰胺基十六烷基磺酸具有大的离子位阻效应,合成的预交联体膨颗粒调剖剂为交联度极大的体型高分子,内部游离的高分子链的含量和分子量很低,增粘效果较差

Benefits of technology

[0124]与现有技术相比,本发明具有如下有益效果:本发明所述缓膨型聚合物微球在老化过程中发生缓慢的溶胀,溶胀程度与清液的荧光强度成线性关系。因此,可以利用荧光测试表征微球的溶胀程度,具有检测灵敏度高、抗干扰能力强等优点,在油井采出水的复杂条件下较粒径测试具有更大的优势。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The application discloses a slow-swelling polymer microsphere, an emulsion of the microsphere, a preparation method of the microsphere and application of the microsphere, wherein the microsphere is a cross-linked polymer microsphere, and the microsphere contains acrylamide structural units, anion monomer structural units, cation monomer structural units and cross-linking structural units; the cross-linking structural units include degradable cross-linking structural units and stable cross-linking structural units. The slow-swelling polymer microsphere has a double cross-linking network structure, one of which is stable cross-linking, and the other is degradable cross-linking; and a small molecule fluorescent substance with fluorescence characteristics is generated after degradation. In this way, the expansion degree of the microsphere can be tested or characterized by detecting the small molecule fluorescent substance generated by degradation. The application uses fluorescence detection instead of particle size testing to characterize the slow-swelling performance of the microsphere, and has good stability, strong anti-interference ability and is beneficial to application in a produced liquid with more impurities on site.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of oilfield development technology, specifically relating to a slow-expanding polymer microsphere, its emulsion, preparation method, and application. Background Technology

[0002] For old oilfields that have been developed with long-term water injection, their heterogeneity will continuously increase, and problems such as water flooding and water channeling will become increasingly prominent. This leads to water injection protruding and fingering along high-permeability layers or fractures between injection wells and production wells, resulting in decreased oil production and increased water cut. To adjust and improve the heterogeneity of the reservoir formation, profile control agents can be injected into the injection wells to plug high-permeability layers. Pre-crosslinked polyacrylamide particles are a commonly used profile control agent. They are nano- or micron-sized, insoluble in water but swell upon contact with water, and are injected with the water to penetrate deep into the formation to plug high-permeability reservoirs.

[0003] CN112279963A discloses a temperature- and salt-resistant multi-component copolymer pre-crosslinked gel particle, its preparation method, and its application, belonging to the fields of petroleum extraction, transportation, and chemical technology. The pre-crosslinked gel particle provided by this invention is copolymerized from acrylamide and 2-acrylamide-2-methylpropanesulfonic acid. The copolymer has a stable structure, good high-temperature aging resistance, is not easily hydrolyzed, and has good compatibility with the polymer. This significantly increases the viscosity of the system and improves the suspension performance of the pre-crosslinked gel particle, resulting in a stronger oil displacement capacity and higher oil displacement efficiency.

[0004] CN105368422A discloses a pre-crosslinked bulk particle profile modifier and its preparation method. The raw materials for synthesizing the pre-crosslinked bulk particle profile modifier, 2-acrylamidooctadecylsulfonic acid or 2-acrylamidohexadecylsulfonic acid, have a large ionic steric hindrance effect. The synthesized pre-crosslinked bulk particle profile modifier is a three-dimensional polymer with a high degree of crosslinking. The content and molecular weight of the internal free polymer chains are very low, resulting in poor thickening effect.

[0005] CN104371679A discloses a bulk-swelling profile control agent for oil production, which has the advantages of high strength, slow water absorption and expansion rate, and good heat resistance. The composition of the bulk-swelling profile control agent for oil production includes: bentonite, perlite, organochromium gel, calcium carbonate, modifier, crosslinking agent, and initiator. The modifier is sodium carbonate, the crosslinking agent is acrylic acid, acrylonitrile, methyl methacrylate, or N,N-methylenebisacrylamide, and the initiator is ammonium persulfate, potassium persulfate, or sodium bisulfite.

[0006] The aforementioned microspheres often swell rapidly in water, easily causing strong blockage in the near-wellbore area, which is not conducive to their penetration into deeper formations. To achieve slow expansion of the microspheres, a double cross-linked network can be introduced into the microspheres, giving them slow expansion properties. This is beneficial for their deep migration and deep profile control within the formation.

[0007] For dual cross-linked network microspheres, it is usually necessary to detect or track their slow expansion process or degree of expansion. Existing technologies typically use particle size testing to characterize the slow expansion ability of slow-expanding microspheres during aging. However, conventional particle size testing uses light scattering, which is a precision test and often has a large error when detecting particle size, especially in salt water or oilfield water with many impurities, where there are many substances that can also cause light scattering, which interferes with the particle size test of microspheres. Summary of the Invention

[0008] To overcome the problems existing in the prior art, this invention provides a slow-swelling polymer microsphere, its emulsion, preparation method, and application. The slow-swelling polymer microsphere has a dual cross-linked network structure, where one cross-linking network is stable and the other is degradable, generating small-molecule fluorescent substances with fluorescence properties after degradation. Thus, the expansion degree of the microspheres can be tested or characterized by detecting the small-molecule fluorescent substances generated during degradation. This invention uses fluorescence detection instead of particle size measurement to characterize the slow-swelling performance of the microspheres, resulting in good stability and strong anti-interference ability, which is beneficial for application in field-collected fluids with high impurity levels.

[0009] One objective of this invention is to provide a slow-expanding polymer microsphere, which is a cross-linked polymer microsphere containing acrylamide structural units, anionic monomer structural units, cationic monomer structural units, and cross-linked structural units, wherein the cross-linked structural units include degradable cross-linked structural units and stable cross-linked structural units.

[0010] The degradable cross-linked structural unit is degradable at high temperatures, while the stable cross-linked structural unit is not degradable.

[0011] The acrylamide structural unit in the slow-expanding polymer microspheres of the present invention has water absorption properties and can absorb water and expand. Furthermore, when the slow-expanding polymer microspheres are in a high-temperature environment (such as 75°C or above), the degradable cross-linked structural units therein will degrade. As the temperature increases, the degree of degradation gradually increases and the degree of cross-linking gradually decreases. As the degree of cross-linking decreases, the water absorption of the microspheres gradually increases, and the microspheres also gradually expand, thus achieving the slow expansion characteristic.

[0012] In a preferred embodiment, the structure of the acrylamide structural unit is shown in formula (I):

[0013]

[0014] In equation (I), R1 is selected from -CONH2 or -R 1 -CONH2, R 1R2, R3, and R4 are each independently selected from hydrogen, alkyl, or substituted alkyl.

[0015] In a further preferred embodiment, in formula (I), R1 is selected from -CONH2 or -R 1 -CONH2, R 1 R2, R3, and R4 are each independently selected from hydrogen, C1-C10 alkyl, C1-C10 substituted alkyl, C6-C10 aromatic or C6-C10 substituted aromatic, and R4 are each independently selected from hydrogen, C1-C10 alkyl or C1-C10 substituted alkyl.

[0016] In a further preferred embodiment, the acrylamide structural unit is formed by polymerization of acrylamide monomers, preferably, the acrylamide monomers are selected from at least one of acrylamide, methacrylamide, and N,N-dimethylacrylamide.

[0017] In a preferred embodiment, the structure of the anionic monomer structural unit is shown in formula (II):

[0018]

[0019] In equation (II), R5 is selected from -(CONH) n -R 2 -COOM or -(CONH) n -R 2 -SO3M, n is 0 or 1, R 2 Selected from hydrogen, alkyl, substituted alkyl, aromatic or substituted aromatic groups, M is selected from hydrogen, alkali metal or NH4. + R6, R7, and R8 are each independently selected from hydrogen, alkyl, or substituted alkyl.

[0020] In a further preferred embodiment, in formula (II), R5 is selected from -(CONH). n -R 2 -COOM or -(CONH) n -R 2 -SO3M, n is 0 or 1, R 2 The group is selected from hydrogen, C1-C10 alkyl, C1-C10 substituted alkyl, C6-C10 aromatic or C6-C10 substituted aromatic, and M is selected from hydrogen, alkali metal or NH4. + R6, R7, and R8 are each independently selected from hydrogen, C1-C10 alkyl groups, or C1-C10 substituted alkyl groups.

[0021] In a further preferred embodiment, the anionic monomer structural unit is formed by polymerization of anionic monomers. Preferably, the anionic monomer is selected from at least one of acrylic acid, methacrylic acid, sodium vinyl sulfonate, p-vinylbenzenesulfonic acid, sodium allyl sulfonate, and sodium 2-acrylamido-2-methylpropanesulfonate.

[0022] In a preferred embodiment, the structure of the cationic monomer structural unit is as shown in formula (III):

[0023]

[0024] In equation (III), R9 is selected from -R 3 -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X or -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X,R 3 R 4 Each is independently selected from alkylene, substituted alkylene, or arylene, R 5 R 6 R 7 Each is independently selected from alkyl, substituted alkyl, aryl, or substituted aryl, m = 0 or 1, R 10 R 11 R 12 Each is independently selected from hydrogen, alkyl, or substituted alkyl.

[0025] In a further preferred embodiment, in formula (III), R9 is selected from -R 3 -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X or -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X,R 3 R 4 Each is independently selected from C1-C10 alkylene, C1-C10 substituted alkylene, C6-C10 arylene, or C6-C10 substituted arylene, R 5 R 6 R 7Each is independently selected from C1-C10 alkyl, C1-C10 substituted alkyl, C6-C10 aryl, or C6-C10 substituted aryl, m = 0 or 1, R 10 R 11 R 12 Each is independently selected from hydrogen, C1-C10 alkyl groups, or C1-C10 substituted alkyl groups.

[0026] In a further preferred embodiment, the cationic monomer structural unit is formed by the polymerization of cationic monomers. Preferably, the cationic monomer is selected from at least one of methacryloyloxyethyltrimethylammonium chloride, 2-acrylamido-2-methylpropyltrimethylammonium chloride, dimethylethylallylammonium chloride, dimethyldiallylammonium chloride, acryloyloxyethyltrimethylammonium chloride, acryloyloxyethyldimethylbenzylammonium chloride, and methacryloyloxyethyldimethylbenzylammonium chloride.

[0027] In a preferred embodiment, the weight ratio of the acrylamide structural unit, the anionic monomer structural unit, and the cationic monomer structural unit is 100:(0-50):(0-50), preferably 100:(0-30):(5-30). For example, the weight ratio of the acrylamide structural unit to the anionic monomer structural unit is 100:0, 100:5, 100:10, 100:15, 100:20, 100:25, 100:30, 100:35, 100:40, 100:45, or 100:50; the weight ratio of the acrylamide structural unit to the cationic monomer structural unit is 100:5, 100:10, 100:15, 100:20, 100:25, 100:30, 100:35, 100:40, 100:45, or 100:50.

[0028] In a preferred embodiment, the degradable crosslinked structural unit contains a fluorescent group and an ester group, preferably, the fluorescent group is a fluorescein group.

[0029] In a further preferred embodiment, the structure of the degradable crosslinking structural unit is selected from the structure shown in formula (IV) or a derivative thereof:

[0030]

[0031] In equation (IV), R 13 R 14 R 16 Each is independently selected from hydrogen, alkyl, substituted alkyl, heteroatom-containing alkyl, or heteroatom-containing substituted alkyl, R 15 Selected from alkylene, substituted alkylene, heteroatom-containing alkylene, or heteroatom-containing substituted alkylene, p = 0 or 1, two Rs 13Whether the two Rs are the same or different 14 Whether the two Rs are the same or different 15 Whether the two Rs are the same or different 16 The two p's may be the same or different; the alkylene group may be a straight-chain alkylene group or a branched alkylene group.

[0032] In a further preferred embodiment, in formula (IV), R 13 R 14 R 16 Each is independently selected from hydrogen, C2-C30 alkyl, C2-C30 substituted alkyl, C2-C30 alkyl containing heteroatoms, or C2-C30 substituted alkyl containing heteroatoms, R 15 Selected from C2-C30 alkylene, C2-C30 substituted alkylene, C2-C30 heteroatom-containing alkylene, and C2-C30 heteroatom-containing substituted alkylene, p = 0 or 1, two Rs 13 Whether the two Rs are the same or different 14 Whether the two Rs are the same or different 15 Whether the two Rs are the same or different 16 Same or different, the two ps are the same or different.

[0033] Preferably, in formula (IV), R 13 R 14 R 16 Each is independently selected from hydrogen, C2-C20 alkyl, C2-C20 substituted alkyl, C2-C20 alkyl containing heteroatoms, or C2-C20 substituted alkyl containing heteroatoms, R 15 Selected from C2-C20 alkylene, C2-C20 substituted alkylene, C2-C20 heteroatom-containing alkylene, and C2-C20 heteroatom-containing substituted alkylene, p = 0 or 1, two Rs 13 Whether the two Rs are the same or different 14 Whether the two Rs are the same or different 15 Whether the two Rs are the same or different 16 Same or different, the two ps are the same or different;

[0034] More preferably, R 13 R 14 R 16 Each is independently selected from hydrogen, C2-C10 alkyl, C2-C10 substituted alkyl, C2-C10 alkyl containing heteroatoms, or C2-C10 substituted alkyl containing heteroatoms, R 15 Selected from C2-C10 alkylene, C2-C10 substituted alkylene, C2-C10 alkylene containing heteroatoms, and C2-C10 substituted alkylene containing heteroatoms; for example: R 13 R 14 R 16 Selected from hydrogen, R15 It is selected from ethylidene, propylidene, isopropylidene, butylidene, or isobutylidene.

[0035] In a further preferred embodiment, the degradable crosslinked structural unit is formed by polymerization of fluorescein-O,O'-dienolate and / or its derivatives, preferably by polymerization of at least one of fluorescein-O,O'-diacrylate and fluorescein-O-O'-dimethacrylate.

[0036] In this invention, when the degradable cross-linked structural unit degrades, it generates a small molecule fluorescent substance (e.g., fluorescein and / or its derivatives). This small molecule fluorescent substance is free in the solution. Therefore, the degree of degradation can be determined by the concentration of the free small molecule fluorescent substance in the solution, thereby obtaining the degree of expansion of the microspheres (specifically, the degree of expansion increases with the degree of degradation). Thus, this invention can detect the expansion of microspheres by detecting the concentration of the free fluorescent substance in the solution (without requiring a precise test like light scattering). Furthermore, the fluorescent properties of the fluorescent substance are specific and exclusive, exhibiting good stability and strong anti-interference ability, which is beneficial for application in field-collected fluids with high levels of impurities.

[0037] In a preferred embodiment, the stable crosslinking structural unit is formed by polymerization of a stable crosslinking agent, the stable crosslinking agent containing at least two reactive groups, the reactive groups being selected from double bonds and / or aldehyde groups.

[0038] In a further preferred embodiment, the stabilizing crosslinking agent is selected from at least one of p-vinylbenzene, 1,4-pentadiene, N,N'-methylenebisacrylamide, N,N'-m-phenylenebismaleimide, formaldehyde, glyoxal, succinaldehyde, glutaraldehyde, adipaldehyde, o-phenylenedialdehyde, azelaic acid, octanedialdehyde, paraformaldehyde, and phenolic prepolymers.

[0039] In a preferred embodiment, based on a total weight of 100 wt% for the acrylamide structural unit, the anionic monomer structural unit, and the cationic monomer structural unit, the amount of the crosslinking structural unit is 0.01 wt% to 0.5 wt%, preferably 0.05 wt% to 0.5 wt%.

[0040] For example, based on a total weight of 100 wt% for the acrylamide structural unit, anionic monomer structural unit, and cationic monomer structural unit, the amount of the crosslinking structural unit is 0.01 wt%, 0.05 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, or 0.5 wt%.

[0041] In a preferred embodiment, based on 100 wt% of the crosslinked structural units, the degradable crosslinked structural units comprise 20–90 wt%, and the stable crosslinked structural units comprise 10–80 wt%.

[0042] For example, based on 100 wt% of the crosslinked structural unit, the degradable crosslinked structural unit is 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, 80 wt%, or 90 wt%, and the stable crosslinked structural unit is 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, or 80 wt%.

[0043] In a further preferred embodiment, based on 100 wt% of the crosslinked structural units, the degradable crosslinked structural units are 30-80 wt%, and the stable crosslinked structural units are 20-70 wt%.

[0044] In a preferred embodiment, the slow-expanding polymer microspheres are obtained by emulsion polymerization of raw materials including the acrylamide monomer, the anionic monomer, the cationic monomer, and the crosslinking agent, wherein the crosslinking agent includes the degradable crosslinking agent and the stable crosslinking agent.

[0045] A second objective of this invention is to provide a slow-swelling polymer microsphere emulsion, comprising a dispersed phase and the polymer microspheres described in one objective of this invention.

[0046] In a preferred embodiment, the dispersed phase comprises an aqueous phase and / or an oil phase.

[0047] In a further preferred embodiment, the oil phase is selected from oil-soluble solvents, preferably from at least one of hydrocarbon solvents and ester solvents.

[0048] In a further preferred embodiment, the hydrocarbon solvent is selected from at least one of aliphatic hydrocarbons, aromatic hydrocarbons, and petroleum fractions; and / or, the ester solvent is selected from at least one of carboxylic acid esters and vegetable oils.

[0049] In a further preferred embodiment: the aliphatic hydrocarbon is selected from C4-C8 aliphatic hydrocarbons, preferably at least one of cyclohexane, hexane, heptane, octane, and isooctane; and / or, the aromatic hydrocarbon is selected from C6-C10 aromatic hydrocarbons, preferably at least one of benzene, toluene, xylene, trimethylbenzene, ethylbenzene, diethylbenzene, and cumene; and / or, the petroleum fraction is selected from at least one of white oil, liquid paraffin, gasoline, kerosene, diesel, and petroleum ether; and / or, the carboxylic acid ester is selected from at least one of C4-C8 monocarboxylic acid esters and C4-C10 diecarboxylic acid esters, preferably at least one of ethyl acetate, propyl acetate, dimethyl oxalate, diethyl oxalate, and methyl ethyl oxalate; and / or, the vegetable oil is selected from at least one of peanut oil, soybean oil, sunflower oil, and castor oil.

[0050] The third objective of this invention is to provide a method for preparing a slow-swelling polymer microsphere emulsion, preferably used to prepare the slow-swelling polymer microsphere emulsion described in the second objective of this invention. The preparation method includes: using components including acrylamide monomers, anionic monomers, cationic monomers, and crosslinking agents as raw materials, and obtaining the slow-swelling polymer microsphere emulsion through emulsion polymerization, wherein the crosslinking agent includes a degradable crosslinking agent and a stable crosslinking agent.

[0051] Preferably, the emulsion polymerization is reverse (micro)emulsion polymerization.

[0052] In a preferred embodiment, the acrylamide monomer is selected from at least one of the compounds shown in formula (i):

[0053]

[0054] In equation (i), R1 is selected from -CONH2 or -R 1 -CONH2, R 1 R2, R3, and R4 are each independently selected from hydrogen, alkyl, or substituted alkyl.

[0055] In a further preferred embodiment, in formula (i), R1 is selected from -CONH2 or -R 1 -CONH2, R 1 R2, R3, and R4 are each independently selected from hydrogen, C1-C10 alkyl, C1-C10 substituted alkyl, C6-C10 aromatic or C6-C10 substituted aromatic, and R4 are each independently selected from hydrogen, C1-C10 alkyl or C1-C10 substituted alkyl.

[0056] In a further preferred embodiment, the acrylamide monomer is selected from at least one of acrylamide, methacrylamide, and N,N-dimethylacrylamide.

[0057] In a preferred embodiment, the anionic monomer is selected from at least one of the compounds shown in formula (ii):

[0058]

[0059] In equation (ii), R5 is selected from -(CONH). n -R 2 -COOM or -(CONH) n -R 2 -SO3M, n is 0 or 1, R 2 Selected from hydrogen, alkyl, substituted alkyl, aromatic or substituted aromatic groups, M is selected from hydrogen, alkali metal or NH4. + R6, R7, and R8 are each independently selected from hydrogen, alkyl, or substituted alkyl.

[0060] In a further preferred embodiment, in formula (ii), R5 is selected from -(CONH). n -R 2 -COOM or -(CONH) n -R 2 -SO3M, n is 0 or 1, R 2 R6, R7, and R8 are each independently selected from hydrogen, C1-C10 alkyl, C1-C10 substituted alkyl, C6-C10 aromatic, or C6-C10 substituted aromatic groups; M is selected from hydrogen, alkali metal, or NH4. + .

[0061] In a further preferred embodiment, the anionic monomer is selected from at least one of acrylic acid, methacrylic acid, sodium vinyl sulfonate, p-vinylbenzenesulfonic acid, sodium allyl sulfonate, and sodium 2-acrylamido-2-methylpropanesulfonate.

[0062] In a preferred embodiment, the cationic monomer is selected from at least one of the compounds shown in formula (iii):

[0063]

[0064] In equation (iii), R9 is selected from -R 3 -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X or -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X,R 3R 4 Each is independently selected from alkylene, substituted alkylene, or arylene, R 5 R 6 R 7 Each is independently selected from alkyl, substituted alkyl, aryl, or substituted aryl, m = 0 or 1, X is selected from anion, R 10 R 11 R 12 Each is independently selected from hydrogen, alkyl, or substituted alkyl.

[0065] In a further preferred embodiment, in formula (iii), R9 is selected from -R 3 -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X or -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X,R 3 R 4 Each is independently selected from C1-C10 alkylene, C1-C10 substituted alkylene, C6-C10 arylene, or C6-C10 substituted arylene, R 5 R 6 R 7 Each is independently selected from C1-C10 alkyl, C1-C10 substituted alkyl, C6-C10 aryl, or C6-C10 substituted aryl, m = 0 or 1, X is selected from halide ions (e.g., chloride, bromide, or iodide ions), R 10 R 11 R 12 Each is independently selected from hydrogen, C1-C10 alkyl groups, or C1-C10 substituted alkyl groups.

[0066] In a further preferred embodiment, the cationic monomer is selected from at least one of methacryloyloxyethyltrimethylammonium chloride, 2-acrylamido-2-methylpropyltrimethylammonium chloride, dimethylethylallylammonium chloride, dimethyldiallylammonium chloride, acryloyloxyethyltrimethylammonium chloride, acryloyloxyethyldimethylbenzylammonium chloride, and methacryloyloxyethyldimethylbenzylammonium chloride.

[0067] In a preferred embodiment, the amount of acrylamide monomer is 100 parts by weight, the amount of anionic monomer is 0 to 50 parts (preferably excluding 0), the amount of cationic monomer is 0 to 50 parts (preferably excluding 0), and the amount of water is 80 to 150 parts.

[0068] For example, by weight, the amount of acrylamide monomer is 100 parts, the amount of anionic monomer is 0, 5, 10, 15, 20, 25, 30, 40 or 50 parts, the amount of cationic monomer is 5, 10, 15, 20, 25, 30, 40 or 50 parts, and the amount of water is 80, 90, 100, 110, 120, 130, 140 or 150 parts.

[0069] In a further preferred embodiment, the amount of acrylamide monomer is 100 parts by weight, the amount of anionic monomer is 0-30 parts, the amount of cationic monomer is 5-30 parts, and the amount of water is 90-120 parts.

[0070] In a preferred embodiment, the degradable crosslinking agent contains a fluorescent group, an ester group, and at least two polymerizable double bonds; preferably, the fluorescent group is a fluorescein group.

[0071] In a further preferred embodiment, the degradable crosslinking agent is selected from at least one of the compounds of formula (iv) or derivatives thereof:

[0072]

[0073] In equation (iv), R 13 R 14 R 16 Each is independently selected from hydrogen, alkyl, substituted alkyl, heteroatom-containing alkyl, or heteroatom-containing substituted alkyl, R 15 Selected from alkylene, substituted alkylene, heteroatom-containing alkylene, or heteroatom-containing substituted alkylene, p = 0 or 1, two Rs 13 Whether the two Rs are the same or different 14 Whether the two R's are the same or different 15 Whether the two R's are the same or different 16 The two p's may be the same or different; the alkylene group may be a straight-chain alkylene group or a branched alkylene group.

[0074] The fluorescence properties are provided by the aromatic ring rather than the pentacyclic ester.

[0075] In a further preferred embodiment, in formula (iv), R 13 R 14 R 16 Each is independently selected from hydrogen, C2-C30 alkyl, C2-C30 substituted alkyl, C2-C30 alkyl containing heteroatoms, or C2-C30 substituted alkyl containing heteroatoms, R 15Selected from C2-C30 alkylene, C2-C30 substituted alkylene, C2-C30 heteroatom-containing alkylene, and C2-C30 heteroatom-containing substituted alkylene, p = 0 or 1, two Rs 13 Whether the two R's are the same or different 14 Whether the two R's are the same or different 15 Whether the two R's are the same or different 16 Same or different, the two ps are the same or different.

[0076] Preferably, in formula (iv), R 13 R 14 R 16 Selected from hydrogen, C2-C20 alkyl, C2-C20 substituted alkyl, C2-C20 alkyl containing heteroatoms, or C2-C20 substituted alkyl containing heteroatoms, R 15 Selected from C2-C20 alkylene, C2-C20 substituted alkylene, C2-C20 heteroatom-containing alkylene, and C2-C20 heteroatom-containing substituted alkylene, more preferably, R 13 R 14 R 16 Selected from hydrogen, C2-C10 alkyl, C2-C10 substituted alkyl, C2-C10 alkyl containing heteroatoms, or C2-C10 substituted alkyl containing heteroatoms, R 15 Selected from C2-C10 alkylene, C2-C10 substituted alkylene, C2-C10 alkylene containing heteroatoms, and C2-C10 substituted alkylene containing heteroatoms; for example: R 13 R 14 R 16 Selected from hydrogen, R 15 It is selected from ethylidene, propylidene, isopropylidene, butylidene, or isobutylidene.

[0077] In a further preferred embodiment, the degradable crosslinking agent is selected from fluorescein-O,O'-dienolate and / or its derivatives, preferably from at least one of fluorescein-O,O'-diacrylate and fluorescein-O-O'-dimethacrylate.

[0078] In a preferred embodiment, the stabilizing crosslinking agent contains at least two reactive groups, which are selected from double bonds and / or aldehyde groups.

[0079] In a further preferred embodiment, the stabilizing crosslinking agent is selected from at least one of p-vinylbenzene, 1,4-pentadiene, N,N'-methylenebisacrylamide, N,N'-m-phenylenebismaleimide, formaldehyde, glyoxal, succinaldehyde, glutaraldehyde, adipaldehyde, o-phenylenedialdehyde, azelaic acid, octanedialdehyde, paraformaldehyde, and phenolic prepolymers.

[0080] In a preferred embodiment, the amount of the crosslinking agent is 0.01 wt% to 0.5 wt%, preferably 0.05 wt% to 0.5 wt%, based on a total weight of 100 wt% of the acrylamide monomers, anionic monomers, and cationic monomers.

[0081] For example, based on a total weight of 100 wt% for the acrylamide monomers, anionic monomers, and cationic monomers, the amount of the crosslinking agent is 0.01 wt%, 0.05 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, or 0.5 wt%.

[0082] In a preferred embodiment, based on a total crosslinking agent content of 100 wt%, the amount of the degradable crosslinking agent is 20-90 wt%, and the amount of the stabilizing crosslinking agent is 10-80 wt%.

[0083] For example, based on a total crosslinking agent content of 100 wt%, the amount of the degradable crosslinking agent is 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, 80 wt%, or 90 wt%, and the amount of the stabilizing crosslinking agent is 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, or 80 wt%.

[0084] In a further preferred embodiment, based on 100 wt% of the crosslinking structural unit, the amount of the degradable crosslinking agent is 30-80 wt%, and the amount of the stable crosslinking structural unit is 20-70 wt%.

[0085] In a preferred embodiment, the preparation method includes: (1) mixing raw material I, including the acrylamide monomer, the anionic monomer, the cationic monomer, the crosslinking agent, and water, to form an aqueous phase; mixing raw material II, including an emulsifier and an oil-soluble solvent, to form an oil phase; and mixing an initiator with water to obtain an initiator solution; (2) emulsifying the aqueous phase and the oil phase to obtain an emulsion mixture; and (3) adding the initiator solution to the emulsion mixture to polymerize and obtain the slow-swelling polymer microsphere emulsion.

[0086] In this invention, the water is deionized water or recycled water.

[0087] In a preferred embodiment, the raw material I may further optionally include a complexing agent and / or an electrolyte salt.

[0088] In a further preferred embodiment, based on a total weight of 100 wt% for the acrylamide monomers, anionic monomers, and cationic monomers, the amount of the complexing agent is 0.01 wt% to 0.5 wt%, and the amount of the electrolyte salt is 0.1 wt% to 5 wt%.

[0089] In a preferred embodiment, the complexing agent is selected from at least one of ethylenediaminetetraacetic acid and its alkali metal salt, and diethylenetriaminepentaacetic acid and its alkali metal salt.

[0090] In a preferred embodiment, the electrolyte salt is selected from at least one of water-soluble inorganic salts and organic acid salts.

[0091] In a further preferred embodiment, the inorganic salt is selected from at least one of alkali metal hydrochloride, alkali metal sulfate, and alkali metal nitrate. Preferably, the alkali metal is selected from lithium, sodium, or potassium. For example, the inorganic salt is selected from at least one of sodium chloride, potassium chloride, sodium sulfate, and potassium sulfate.

[0092] In a further preferred embodiment, the organic acid salt is selected from alkali metal organic acid salts, preferably from alkali metal salts of C2-C6 carboxylic acids, and more preferably, the alkali metal is selected from lithium, sodium or potassium, for example, the organic acid salt is sodium acetate.

[0093] In a preferred embodiment, the pH value of the aqueous phase is 7 to 11.

[0094] In a preferred embodiment, the oil-soluble solvent is selected from at least one of hydrocarbon solvents and ester solvents.

[0095] In a further preferred embodiment, the hydrocarbon solvent is selected from at least one of aliphatic hydrocarbons, aromatic hydrocarbons, and petroleum fractions; and / or, the ester solvent is selected from at least one of carboxylic acid esters and vegetable oils.

[0096] In a further preferred embodiment: the aliphatic hydrocarbon is selected from C4-C8 aliphatic hydrocarbons, preferably at least one of cyclohexane, hexane, heptane, octane, and isooctane; and / or, the aromatic hydrocarbon is selected from C6-C10 aromatic hydrocarbons, preferably at least one of benzene, toluene, xylene, trimethylbenzene, ethylbenzene, diethylbenzene, and cumene; and / or, the petroleum fraction is selected from at least one of white oil, liquid paraffin, gasoline, kerosene, diesel, and petroleum ether; and / or, the carboxylic acid ester is selected from at least one of C4-C8 monocarboxylic acid esters and C4-C10 diecarboxylic acid esters, preferably at least one of ethyl acetate, propyl acetate, dimethyl oxalate, diethyl oxalate, and methyl ethyl oxalate; and / or, the vegetable oil is selected from at least one of peanut oil, soybean oil, sunflower oil, and castor oil.

[0097] In a preferred embodiment, the emulsifier is a single emulsifier or a mixture of multiple emulsifiers with different HLB values, wherein the HLB value of the single emulsifier or the mixture of emulsifiers is 5 to 9.

[0098] In a further preferred embodiment, the emulsifier is selected from at least one of fatty alcohols, alkylphenols, fatty acids, fatty acid esters, alkoxy adducts of amines, and polyol (partial) hydroxyl carboxylation or esterification products.

[0099] In a further preferred embodiment, the emulsifier is selected from a mixture of nonionic surfactants with an HLB of 1 to 7 and nonionic surfactants with an HLB of 8 to 18.

[0100] Preferably, the nonionic surfactant with an HLB of 1 to 7 is selected from at least one of fatty alcohol polyoxyethylene ether (AEO1 to 5), sorbitan tristearate (SPAN65), sorbitan trioleate (SPAN85), isomeric alcohol polyoxyethylene ether (TO3, TO5), and fatty acid polyoxyethylene ester; the nonionic surfactant with an HLB of 8 to 18 is selected from at least one of fatty alcohol polyoxyethylene ether (AEO10 to 20), alkylphenol polyoxyethylene ether (OP10), sorbitan monolaurate (SPAN20), isomeric alcohol polyoxyethylene ether (TO8, TO12, TO30, TO40), fatty amine polyoxyethylene ether, and polyoxyethylene dehydrated sorbitan fatty acid ester (TWEEN20 to 80).

[0101] In a preferred embodiment, the emulsifier content is 5 wt% to 35 wt%, preferably 10 wt% to 25 wt%, based on 100 wt% of the oil phase.

[0102] For example, based on 100 wt% of the oil phase, the content of the emulsifier is 5 wt%, 10 wt%, 15 wt%, 20 wt%, 25 wt%, 30 wt%, or 35 wt%.

[0103] In a preferred embodiment, the initiator is selected from oxidant-reducant initiation systems and / or azo initiators.

[0104] In a further preferred embodiment, the oxidant is selected from at least one of water-soluble and oil-soluble oxidants, preferably from at least one of potassium persulfate, sodium persulfate, ammonium persulfate, benzoyl peroxide, and tert-butyl hydroperoxide; and / or, the reducing agent is selected from at least one of water-soluble and oil-soluble reducing agents, preferably from at least one of sodium sulfite, potassium sulfite, sodium bisulfite, sodium bisulfite, sodium thiosulfate, ferrous chloride, and ferrous ammonium sulfate; and / or, the azo compound is selected from water-soluble azo compounds. At least one of nitrogen compounds and oil-soluble azo compounds, preferably, the water-soluble azo compound is selected from at least one of azobisisobutyranidine hydrochloride, 2,2'-azo[2-(2-imidazolin-2-yl)propane] dihydrochloride, 4,4'-azobis(4-cyanopentaic acid) salt, and azobis(2,5-dimethyl-6-carboxy)hexane, and / or, the oil-soluble azo compound is selected from at least one of azobisisobutyronitrile, azobisisovalerate, azobisisoheptanenitrile, and dimethyl azobisisobutyrate.

[0105] In a preferred embodiment, the amount of the initiator is 0.02 wt% to 0.3 wt%, based on a total weight of 100 wt% of the acrylamide monomers, anionic monomers, and cationic monomers.

[0106] For example, based on a total weight of 100 wt% for the acrylamide monomers, anionic monomers, and cationic monomers, the amount of the initiator is 0.02 wt%, 0.05 wt%, 0.1 wt%, 0.15 wt%, 0.2 wt%, 0.25 wt%, or 0.3 wt%.

[0107] In a preferred embodiment, when the initiator is selected from an oxidant-reducing initiation system, the weight ratio of the oxidant to the reducing agent is 1:(0.1 to 10), preferably 1:(0.5 to 2), for example 1:0.1, 1:0.5, 1:1, 1:2, 1:4, 1:6, 1:8 or 1:10.

[0108] In a further preferred embodiment, when the initiator is selected from an oxidant-reducant initiation system, the oxidant is added to the aqueous phase, and the reducing agent is mixed with water to form the initiator solution.

[0109] In a preferred embodiment, the emulsion polymerization temperature is 20–100°C (e.g., 20°C, 40°C, 60°C, 80°C, or 100°C), and / or the time is 1–3 h (e.g., 1 h, 1.5 h, 2 h, 2.5 h, or 3 h).

[0110] The temperature of the polymerization reaction can be controlled by using a water bath.

[0111] In a further preferred embodiment, the emulsion polymerization is carried out under a protective atmosphere; preferably, a protective gas is introduced to remove oxygen before and during polymerization until the polymerization reaction is completed; more preferably, the protective gas is selected from nitrogen and / or an inert gas.

[0112] The fourth objective of this invention is to provide a method for preparing slow-swelling polymer microspheres, preferably for preparing the slow-swelling polymer microspheres described in the first objective of this invention. The preparation method includes: (A) dispersing the slow-swelling polymer microsphere emulsion described in the second objective of this invention or the slow-swelling polymer microsphere emulsion obtained by the preparation method described in the third objective of this invention in an alcohol solvent, stirring thoroughly, and then filtering to remove solid I; (B) redispersing solid I in an alcohol solvent, stirring thoroughly, and then filtering to remove solid II; (C) drying solid II to obtain the slow-swelling polymer microspheres.

[0113] In a preferred embodiment, the alcohol solvent is selected from methanol and / or ethanol, preferably ethanol, such as anhydrous ethanol.

[0114] In a preferred embodiment, the slow-swelling polymer microsphere emulsion is added dropwise to the alcohol solvent.

[0115] In a further preferred embodiment, based on 300-400 mL of alcohol solvent, the added slow-swelling polymer microsphere emulsion is 10-50 g, preferably 20-30 g, for example 10 g, 20 g, 30 g, 40 g or 50 g.

[0116] In a preferred embodiment, the drying process is natural air drying or oven drying, etc.

[0117] In a preferred embodiment, the slow-swelling polymer microspheres are obtained as follows:

[0118] (1) Add 300-400 mL of alcohol solvent to a beaker and place it on a magnetic stirrer (e.g., turn on the speed at 400±20 rpm);

[0119] (2) The slow-swelling polymer microsphere emulsion obtained by the preparation method described in the third objective of this invention is added dropwise to the alcohol solvent (e.g., ethanol) in step (1), and a total of 10-50g of emulsion is added. The mixture is stirred continuously for 90min to obtain an alcohol solvent dispersion of microspheres.

[0120] (3) Vacuum filter the alcohol solvent dispersion obtained in step (2), and redisperse the filtered solid in the alcohol solvent and stir continuously (e.g., for 90 min) to obtain the alcohol solvent redisperse of microspheres.

[0121] (4) The alcohol solvent redispersed liquid obtained in step (3) is vacuum filtered, and the filtered solid is placed in an oven (e.g., 50°C) and dried for 15-60 min (preferably 30-45 min) to obtain the slow-swelling polymer microspheres.

[0122] The fifth objective of this invention is to provide the application of the slow-expanding polymer microspheres described in the first objective of this invention, the slow-expanding polymer microsphere emulsion described in the first objective of this invention, the slow-expanding polymer microsphere emulsion obtained by the preparation method described in the third objective of this invention, or the slow-expanding polymer microspheres obtained by the preparation method described in the fourth objective of this invention in the field of oilfield development.

[0123] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values; these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. In the following, various technical solutions can, in principle, be combined with each other to obtain new technical solutions, which should also be considered as specifically disclosed herein.

[0124] Compared with existing technologies, the present invention has the following advantages: the slow-swelling polymer microspheres of the present invention undergo slow swelling during the aging process, and the degree of swelling is linearly related to the fluorescence intensity of the clear liquid. Therefore, the degree of swelling of the microspheres can be characterized by fluorescence testing, which has the advantages of high detection sensitivity and strong anti-interference ability, and has greater advantages than particle size testing under the complex conditions of oil well produced water. Attached Figure Description

[0125] Figure 1 The fluorescence standard curve is shown.

[0126] Figures 2-5 These are Examples 1 through 4. 1 H-NMR spectrum;

[0127] exist Figures 2-5 In the figure, the horizontal axis represents ppm. Detailed Implementation

[0128] The present invention will now be described in detail with reference to specific embodiments. It should be noted that the following embodiments are only used to further illustrate the present invention and should not be construed as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the content of the present invention are still within the scope of protection of the present invention.

[0129] It should also be noted that the various specific technical features described in the following embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the various possible combinations will not be described separately in this invention.

[0130] Furthermore, various embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention. The resulting technical solutions are part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0131] Unless otherwise specified, the raw materials used in the examples and comparative examples are all disclosed in the prior art, such as those that can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0132] Example 1: Preparation of Microsphere Emulsion

[0133] (1) Dissolve 7 parts of a composite emulsifier with an HLB value of 5.3 (a mixture of Span 80 and Tween 20) in 50 parts of white oil and stir until homogeneous to obtain the oil phase.

[0134] (2) Dissolve 40 parts of acrylamide, 5 parts of methacryloyloxyethyltrimethylammonium chloride, and 5 parts of 2-acrylamido-dimethylpropanesulfonic acid in 45 parts of water. Based on the total weight percentage of all monomers, dissolve 0.03% of disodium ethylenediaminetetraacetate, 0.3% of sodium acetate, 0.2% of N,N'-methylenebisacrylamide, 0.1% of fluorescein-O,O'-diacrylate, and 0.05% of potassium persulfate in the above monomer solution. Adjust the pH of the aqueous phase to 8 with sodium hydroxide solution to obtain the aqueous phase. Dissolve 0.05% of sodium bisulfite in 5 parts of water to obtain a reducing initiator aqueous solution.

[0135] (3) Pour the aqueous phase into the oil phase, emulsify it and add it to the reactor. Stir at 500 r / min and purge with nitrogen for 30 min to remove oxygen. Keep the water bath temperature at 25℃. Add the reducing initiator aqueous solution to the reactor, purge with nitrogen and stir until the polymerization reaction is complete (total time 60 min) and keep warm for 40 min to obtain the slow-swelling polymer microsphere emulsion.

[0136] The slow-swelling polymer microsphere emulsion was dispersed with anhydrous ethanol, the solid was filtered out, redispersed with anhydrous ethanol, the solid was filtered out again, and then dried to obtain slow-swelling polymer microspheres.

[0137] Example 2: Preparation of microsphere emulsion

[0138] (1) Dissolve 12 parts of a composite emulsifier with an HLB value of 6.0 (a mixture of Span 80 and OP10) in 45 parts of the white oil and stir until homogeneous to obtain the oil phase.

[0139] (2) Dissolve 40 parts of acrylamide and 8 parts of methacryloyloxyethyltrimethylammonium chloride in 45 parts of water. According to the total weight percentage of all monomers, dissolve 0.08% of disodium ethylenediaminetetraacetate, 0.5% of sodium acetate, 0.1% of N,N'-methylenebisacrylamide, and 0.4% of fluorescein-O-O'-dimethacrylate in the above monomer solution. Adjust the pH of the aqueous phase to 7 with sodium hydroxide solution to obtain an aqueous phase. Dissolve 0.1% of azobisisobutylamidine hydrochloride in 5 parts of water to obtain an initiator aqueous solution.

[0140] (3) Pour the aqueous phase into the oil phase, emulsify it and add it to the reactor. Stir at 500 r / min and purge with nitrogen for 30 min to remove oxygen. Keep the water bath temperature at 50℃. Add the initiator aqueous solution to the reactor, purge with nitrogen and stir until the polymerization reaction is complete (total time 90 min) and keep warm for 40 min to obtain the slow-swelling polymer microsphere emulsion.

[0141] The slow-swelling polymer microsphere emulsion was dispersed with anhydrous ethanol, the solid was filtered out, redispersed with anhydrous ethanol, the solid was filtered out again, and then dried to obtain slow-swelling polymer microspheres.

[0142] Example 3: Preparation of Microsphere Emulsion

[0143] (1) Dissolve 15 parts of a composite emulsifier with an HLB value of 6.2 (a mixture of SPAN80 and TO8) in 60 parts of the white oil and stir until homogeneous to obtain the oil phase.

[0144] (2) Dissolve 40 parts acrylamide, 5 parts methacrylamide, and 10 parts methacryloxyethyltrimethylammonium chloride in 45 parts water. Based on the total weight percentage of all monomers, dissolve 0.18% disodium ethylenediaminetetraacetate, 0.5% sodium acetate, 0.05% ammonium persulfate, 0.3% N,N'-methylenebisacrylamide, and 0.2% fluorescein-O-O'-dimethylacrylate in the above monomer solution. Adjust the pH of the aqueous phase to 7 with sodium hydroxide solution to obtain the aqueous phase. Dissolve 0.05% sodium bisulfite in 5 parts water to obtain a reducing initiator aqueous solution.

[0145] (3) Pour the aqueous phase into the oil phase, emulsify it and add it to the reactor. Stir at 500 r / min and purge with nitrogen for 30 min to remove oxygen. Keep the water bath temperature at 25℃. Add the reducing initiator aqueous solution to the reactor, purge with nitrogen and stir until the polymerization reaction is complete (total time 65 min) and keep warm for 40 min to obtain the slow-swelling polymer microsphere emulsion.

[0146] The slow-swelling polymer microsphere emulsion was dispersed with anhydrous ethanol, the solid was filtered out, redispersed with anhydrous ethanol, the solid was filtered out again, and then dried to obtain slow-swelling polymer microspheres.

[0147] Example 4: Preparation of Microsphere Emulsion

[0148] (1) Dissolve 10 parts of a composite emulsifier with an HLB value of 6.0 (a mixture of AEO3 and TO12) in 40 parts of the white oil and stir until homogeneous to obtain the oil phase.

[0149] (2) Dissolve 35 parts of acrylamide, 5 parts of N'N-dimethylacrylamide, and 8 parts of methacryloyloxyethyltrimethylammonium chloride in 40 parts of water. Based on the total weight percentage of all monomers, dissolve 0.25% of disodium ethylenediaminetetraacetate, 0.2% of N,N'-methylenebisacrylamide, and 0.2% of fluorescein-O-O'-dimethacrylate in the above monomer solution. Adjust the pH of the aqueous phase to 7 with sodium hydroxide solution to obtain the aqueous phase. Dissolve 0.1% of sodium azobis(2,5-dimethyl-6-carboxy)hexanoate in 5 parts of water to obtain an initiator aqueous solution.

[0150] (3) Pour the aqueous phase into the oil phase, emulsify it and add it to the reactor. Stir at 500 r / min and purge with nitrogen for 30 min to remove oxygen. Keep the water bath temperature at 50℃. Add the initiator aqueous solution to the reactor, purge with nitrogen and stir until the polymerization reaction is complete (total time 80 min), and keep warm for 40 min to obtain the slow-swelling polymer microsphere emulsion.

[0151] The slow-swelling polymer microsphere emulsion was dispersed with anhydrous ethanol, the solid was filtered out, redispersed with anhydrous ethanol, the solid was filtered out again, and then dried to obtain slow-swelling polymer microspheres.

[0152] Example 5: Preparation of Microsphere Emulsion

[0153] (1) Dissolve 7 parts of a composite emulsifier with an HLB value of 5.3 (a mixture of Span 80 and Tween 20) in 50 parts of white oil and stir until homogeneous to obtain the oil phase.

[0154] (2) Dissolve 40 parts of acrylamide and 12 parts of 2-acrylamido-2-methylpropyltrimethylammonium chloride in 36 parts of water. According to the total weight percentage of all monomers, continue to dissolve 0.03% of sodium diethylenetriaminepentaacetate, 0.3% of sodium formate, 0.035% of N,N'-methylenebisacrylamide, and 0.015% of fluorescein-O,O'-diacrylate in the above monomer solution. Adjust the pH of the aqueous phase to 8 with sodium hydroxide solution to obtain an aqueous phase. Dissolve 0.02% of sodium azobis(2,5-dimethyl-6-carboxy)hexanoate in 5 parts of water to obtain an initiator aqueous solution.

[0155] (3) Pour the aqueous phase into the oil phase, emulsify it and add it to the reactor. Stir at 500 r / min and purge with nitrogen for 30 min to remove oxygen. Keep the water bath temperature at 50℃. Add the initiator aqueous solution to the reactor, purge with nitrogen and stir until the polymerization reaction is complete (total time 90 min) and keep warm for 40 min to obtain the slow-swelling polymer microsphere emulsion.

[0156] The slow-swelling polymer microsphere emulsion was dispersed with anhydrous ethanol, the solid was filtered out, redispersed with anhydrous ethanol, the solid was filtered out again, and then dried to obtain slow-swelling polymer microspheres.

[0157] Example 6: Preparation of Microsphere Emulsion

[0158] (1) Dissolve 7 parts of a composite emulsifier with an HLB value of 5.3 (a mixture of Span 80 and Tween 20) in 50 parts of white oil and stir until homogeneous to obtain the oil phase.

[0159] (2) Dissolve 40 parts acrylamide, 2 parts dimethyl ethyl allyl ammonium chloride, and 12 parts 2-acrylamido-dimethylpropanesulfonic acid in 45 parts water. Based on the total weight percentage of all monomers, dissolve 0.03% disodium ethylenediaminetetraacetate, 0.3% potassium acetate, 0.14% N,N'-methylenebisacrylamide, and 0.36% fluorescein-O,O'-diacrylate in the above monomer solution. Adjust the pH of the aqueous phase to 8 with sodium hydroxide solution to obtain the aqueous phase. Dissolve 0.3% sodium azobis(2,5-dimethyl-6-carboxy)hexanoate in 5 parts water to obtain the initiator aqueous solution.

[0160] (3) Pour the aqueous phase into the oil phase, emulsify it and add it to the reactor. Stir at 500 r / min and purge with nitrogen for 30 min to remove oxygen. Keep the water bath temperature at 50℃. Add the initiator aqueous solution to the reactor, purge with nitrogen and stir until the polymerization reaction is complete (total time 85 min), and keep warm for 40 min to obtain the slow-swelling polymer microsphere emulsion.

[0161] The slow-swelling polymer microsphere emulsion was dispersed with anhydrous ethanol, the solid was filtered out, redispersed with anhydrous ethanol, the solid was filtered out again, and then dried to obtain slow-swelling polymer microspheres.

[0162] Experimental Example 1: Microspheres 1 H-NMR test

[0163] The slow-expanding polymer microspheres described in Examples 1 to 4 were used.

[0164] Weigh 0.01–0.02 g of slow-swelling polymer microspheres into a petri dish, dry them in a vacuum oven at 120 °C for 120 min, then disperse the dried polymer microspheres in 5 mL of D₂O and stir thoroughly to obtain a D₂O dispersion of the slow-swelling polymer microspheres. Test the dispersion using a JNM 500 MHz NMR spectrometer or a similar instrument. 1 H-NMR.

[0165] Figures 2-5 These are Examples 1 through 4. 1 H-NMR spectrum.

[0166] Example 2: Construction of the fluorescence standard curve

[0167] Standard solutions of fluorescein at different concentrations were prepared using simulated saline with a mineralization of 8300 mg / L. The solutions were then subjected to 3D scanning using a Hitachi F-7000 fluorescence spectrophotometer, and the maximum excitation wavelength λ of the fluorescence was determined. ex =480nm, maximum emission wavelength λ em =512nm. The fluorescence standard curve of fluorescein is as follows: Figure 1 As shown, the fluorescence intensity is linearly related to the concentration in the range of 0.05–0.95 ppm.

[0168] In Experiments 2-4, samples were taken after aging for different times, the supernatant was centrifuged, and its fluorescence intensity was tested. The concentration of fluorescein was obtained according to the fluorescence standard curve in this experiment, and the degradation rate of the degradable crosslinking agent was calculated according to Equation (1):

[0169] D f =C ft / C f0 ×100% (1)

[0170] In the formula, D f The degradation rate of the fluorescent crosslinking agent, in %; C ft The concentration of fluorescent substances in the obtained clear solution is measured in ppm; C f0 The total concentration (ppm) of the fluorescent substance in the solution of the microspheres, calculated during solution preparation, is obtained using equation (2):

[0171]

[0172] In the formula, C f0 The concentration of the fluorescent crosslinking agent in the solution is in ppm; W f The weight (g) of the fluorescent crosslinking agent used to synthesize the polymer microsphere emulsion in the examples; W water The weight of deionized water used to synthesize the polymer microsphere emulsion in the examples is in g; W oilThe weight of the oil-soluble solvent used to synthesize the polymer microsphere emulsion in the examples is in g; W total The total weight (g) of materials other than water and oil-soluble solvents used in the synthesis of the polymer microsphere emulsion in the examples; C solution The concentration of the microsphere emulsion prepared in the experimental or comparative examples is expressed in ppm.

[0173] The expansion degree of the microspheres is calculated according to equation (3):

[0174] E f =C total / (C total -C ft )-1 (3)

[0175] In the formula, E f C represents the microsphere swelling degree calculated based on fluorescence intensity. total C represents the total crosslinking agent concentration in the solution, in ppm. ft The concentration of fluorescent substances in the obtained clear solution is given in ppm. Where C... total The result is obtained by calculation using equation (4):

[0176]

[0177] In the formula, C total W represents the total crosslinking agent concentration in the solution, in ppm. cross-linking The total amount of crosslinking agent used in the synthesis of the polymer microsphere emulsion in the examples, in grams, includes degradable crosslinking agents and stable crosslinking agents; W water The weight of deionized water used to synthesize the polymer microsphere emulsion in the examples is in g; W oil The weight of the oil-soluble solvent used to synthesize the polymer microsphere emulsion in the examples is in g; W total The total weight (g) of materials other than water and oil-soluble solvents used in the synthesis of the polymer microsphere emulsion in the examples; C solution The concentration of the polymer microsphere emulsion prepared in the experimental or comparative examples is expressed in ppm.

[0178] Experiment Example 3: Test of the Slow Expansion Performance of Microspheres

[0179] (1) The microsphere emulsion prepared in Example 1 was dispersed in simulated saline with a mineralization of 8300 mg / L to obtain a solution with a microsphere emulsion concentration of 4000 ppm, wherein the content of the fluorescent crosslinking agent fluorescein-O,O'-diacrylate was C f0 The total crosslinking agent concentration was 1.27 ppm. total The concentration was 3.81 ppm. The microsphere solution was aged in a 70°C oven, causing the fluorescein-O,O'-diacrylate structural units to hydrolyze into fluorescein. The fluorescence intensity and calculated expansion after aging for different times are shown in Table 1.

[0180] Table 1:

[0181] Fluorescein concentration (ppm) 0.050 0.093 0.126 0.354 0.561 Crosslinking agent degradation rate 3.94% 7.32% 9.92% 27.87% 44.17% <![CDATA[Microsphere swelling degree (E f )]]> 0.013 0.025 0.034 0.102 0.173

[0182] (2) The microsphere emulsion prepared in Example 2 was dispersed in simulated saline with a mineralization of 8300 mg / L to obtain a solution with a microsphere emulsion concentration of 2000 ppm, wherein the content of the fluorescent crosslinking agent fluorescein-O,O'-dimethacrylate was C f0 The total crosslinking agent concentration was 2.47 ppm. total The concentration was 3.09 ppm. The microsphere solution was aged in a 70°C oven, causing the fluorescein-O,O'-dimethacrylate structural unit to hydrolyze into fluorescein. The fluorescence intensity and calculated expansion after aging for different times are shown in Table 2.

[0183] Table 2:

[0184] Fluorescein concentration (ppm) 0.081 0.164 0.205 0.613 0.942 Crosslinking agent degradation rate 3.27% 6.63% 8.30% 24.82% 38.14% <![CDATA[Microsphere swelling degree (E f )]]> 0.027 0.056 0.071 0.247 0.439

[0185] Anti-interference performance of Experiment Example 4: Slow Expansion Test

[0186] (1) The microsphere emulsion prepared in Example 1 was dispersed in field water from the Henan Oilfield with a salinity of 8300 mg / L to obtain a solution with a microsphere emulsion concentration of 4000 ppm, wherein the content of the fluorescent crosslinking agent fluorescein-O,O'-diacrylate was C f0 The total crosslinking agent concentration was 1.27 ppm. total The value was 3.81 ppm. Samples were taken after aging at 70℃ for different times. The fluorescence intensity and calculated expansion degree obtained from the samples after different aging times are shown in Table 3. The obtained data are close to those in Table 1. The evaluation results of the microspheres' expansion in field water are not significantly different from those in simulated brine, indicating that this test method has good anti-interference properties in oilfield produced water.

[0187] Table 3:

[0188] Fluorescein concentration (ppm) 0.048 0.086 0.130 0.347 0.557 Crosslinking agent degradation rate 3.78% 6.77% 10.24% 27.32% 43.85% <![CDATA[Microsphere swelling degree (E f )]]> 0.013 0.023 0.035 0.100 0.171

[0189] (2) The microsphere emulsion prepared in Example 2 was dispersed in produced water from the Henan Oilfield with a salinity of 8300 mg / L to obtain a solution with a microsphere emulsion concentration of 2000 ppm, wherein the content of the fluorescent crosslinking agent fluorescein-O,O'-dimethacrylate was C f0 The total crosslinking agent concentration was 1.27 ppm. totalThe value was 3.81 ppm. Samples were taken after aging at 70℃ for different times. The fluorescence intensity and calculated expansion degree obtained from the samples after different aging times are shown in Table 4. The obtained data are close to those in Table 2. The evaluation results of the microspheres' expansion in field water are not significantly different from those in simulated brine, indicating that this test method has good anti-interference properties in oilfield produced water.

[0190] Table 4:

[0191] Fluorescein concentration (ppm) 0.084 0.170 0.199 0.597 0.957 Crosslinking agent degradation rate 3.40% 6.88% 8.06% 24.17% 38.74% <![CDATA[Microsphere swelling degree (E f )]]> 0.027 0.058 0.068 0.239 0.449

[0192] Comparative Experiment Example 1: Interference Resistance of Particle Size Detection

[0193] In this comparative example, the fluorescence intensity of the solution is not measured; instead, the particle size of the microspheres is measured. The degree of expansion of the microspheres is calculated based on the expansion of the particle size, as shown in Equation 5.

[0194]

[0195] In the formula, E d D represents the microsphere expansion calculated based on particle size expansion. t D0 is the particle size of the microspheres after aging for t days, in nm; D0 is the initial particle size of the microspheres, in nm; t is the aging time, in days; D0 is the particle size of the microspheres after aging for t days, in nm. t / D0 is the microsphere expansion factor; C ms C represents the total concentration of monomers polymerized into microspheres in solution, in ppm; total 12.2 is the total crosslinking agent concentration in the solution, in ppm; 12.2 is an empirical constant.

[0196] (1) The microsphere emulsion prepared in Example 1 was dispersed in simulated saline with a mineralization of 8300 mg / L to obtain a solution with a microsphere emulsion concentration of 4000 ppm, wherein the content of the fluorescent crosslinking agent fluorescein-O,O'-diacrylate was C f0 The total crosslinking agent concentration was 1.27 ppm. total The concentration was 3.81 ppm. The microsphere solution was aged in a 70°C oven. The particle size of the microspheres was measured using a particle size analyzer, and the expansion degree was calculated based on the particle size. The results are shown in Table 5.

[0197] Table 5:

[0198] Microsphere expansion factor 3.752 5.069 6.098 7.931 8.663 <![CDATA[Microsphere swelling degree (E d )]]> 0.013 0.032 0.056 0.123 0.160

[0199] (2) The microsphere emulsion prepared in Example 1 was dispersed in produced water from the Henan Oilfield with a salinity of 8300 mg / L to obtain a solution with a microsphere emulsion concentration of 4000 ppm, wherein the content of the fluorescent crosslinking agent fluorescein-O,O'-diacrylate was C f0 The total crosslinking agent concentration was 1.27 ppm. totalThe concentration was 3.81 ppm. Samples were taken after aging at 70℃ for different times, and the microsphere particle size was measured. The expansion degree of the microspheres was calculated based on the particle size, and the results are shown in Table 6. The obtained data differed significantly from the data in Table 5. The evaluation results of the microspheres in the field water differed greatly from the results in the simulated brine, indicating that this testing method has poor anti-interference ability in oilfield produced water.

[0200] Table 6:

[0201] Microsphere expansion factor 4.980 10.366 7.921 8.634 9.723 <![CDATA[Microsphere swelling degree (E d )]]> 0.030 0.274 0.122 0.158 0.226

[0202] The present invention has been described in detail above with reference to specific embodiments and exemplary examples; however, these descriptions should not be construed as limiting the present invention. Those skilled in the art will understand that various equivalent substitutions, modifications, or improvements can be made to the technical solutions and embodiments of the present invention without departing from the spirit and scope of the invention, and all such modifications and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the appended claims.

Claims

1. A slow-expanding polymer microsphere, which is a cross-linked polymer microsphere, comprising acrylamide structural units, anionic monomer structural units, cationic monomer structural units and cross-linked structural units, wherein the cross-linked structural units include degradable cross-linked structural units and stable cross-linked structural units; The structure of the anionic monomer structural unit is shown in formula (II): Equation (II) In equation (II), R5 is selected from -(CONH). n -R 2 -COOM or -(CONH) n -R 2 -SO3M, n is 0 or 1, R 2 Selected from hydrogen, alkyl, substituted alkyl, aromatic or substituted aromatic groups, M is selected from hydrogen, alkali metal or NH4. + R6, R7, and R8 are each independently selected from hydrogen, alkyl, or substituted alkyl groups; The structure of the cationic monomer structural unit is shown in formula (III): Equation (III) In equation (III), R9 is selected from -R 3 -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X or -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X,R 3 R 4 Each is independently selected from alkylene, substituted alkylene, or arylene, R 5 R 6 R 7 Each is independently selected from alkyl, substituted alkyl, aryl, or substituted aryl, m=0 or 1, X is selected from anion, R 10 R 11 R 12 Each is independently selected from hydrogen, alkyl, or substituted alkyl; The weight ratio of the acrylamide structural unit, the anionic monomer structural unit, and the cationic monomer structural unit is 100:(0~50):(0~50), and the weight ratio of the anionic monomer structural unit and the cationic monomer structural unit is not 0. The biodegradable crosslinked structural unit contains fluorescent groups and ester groups.

2. The slowly expanding polymer microspheres according to claim 1, characterized in that, The structure of the acrylamide structural unit is shown in formula (I): Equation (I) In equation (I), R1 is selected from -CONH2 or -R 1 -CONH2, R 1 R2, R3, and R4 are each independently selected from hydrogen, alkyl, or substituted alkyl.

3. The slowly expanding polymer microspheres according to claim 2, characterized in that, In equation (I), R1 is selected from -CONH2 or -R 1 -CONH2, R 1 R2, R3, and R4 are each independently selected from hydrogen, C1-C10 alkyl, C1-C10 substituted alkyl, C6-C10 aryl, or C6-C10 substituted aryl, and R4 are each independently selected from hydrogen, C1-C10 alkyl, or C1-C10 substituted alkyl; and / or, In equation (II), R5 is selected from -(CONH). n -R 2 -COOM or -(CONH) n -R 2 -SO3M, n is 0 or 1, R 2 Selected from hydrogen, C1-C10 alkyl, C1-C10 substituted alkyl, C6-C10 aryl, or C6-C10 substituted aryl, M is selected from hydrogen, alkali metal, or NH4. + R6, R7, and R8 are each independently selected from hydrogen, C1-C10 alkyl groups, or C1-C10 substituted alkyl groups; and / or, In equation (III), R9 is selected from -R 3 -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X or -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X,R 3 R 4 Each is independently selected from C1-C10 alkylene, C1-C10 substituted alkylene, C6-C10 arylene, or C6-C10 substituted arylene, R 5 R 6 R 7 Each is independently selected from C1-C10 alkyl, C1-C10 substituted alkyl, C6-C10 aryl, or C6-C10 substituted aryl, m=0 or 1, R 10 R 11 R 12 Each is independently selected from hydrogen, C1-C10 alkyl groups, or C1-C10 substituted alkyl groups.

4. The slowly expanding polymer microspheres according to claim 1, characterized in that, The weight ratio of the acrylamide structural unit, the anionic monomer structural unit, and the cationic monomer structural unit is 100:(0~30):(5~30), and the weight ratio of the anionic monomer structural unit and the cationic monomer structural unit is not 0.

5. The slowly expanding polymer microspheres according to claim 1, characterized in that, The fluorescent group is a fluorescein group.

6. The slowly expanding polymer microspheres according to claim 1, characterized in that, The structure of the degradable crosslinking structural unit is selected from the structure shown in formula (IV) or its derivative structure: Formula (IV); In equation (IV), R 13 R 14 R 16 Each is independently selected from hydrogen, alkyl, substituted alkyl, heteroatom-containing alkyl, or heteroatom-containing substituted alkyl, R 15 Selected from alkylene, substituted alkylene, heteroatom-containing alkylene, or heteroatom-containing substituted alkylene, p=0 or 1, two Rs 13 Whether the two R's are the same or different 14 Whether the two R's are the same or different 15 Whether the two R's are the same or different 16 Same or different, the two ps are the same or different.

7. The slowly expanding polymer microspheres according to claim 6, characterized in that, In equation (IV), R 13 R 14 R 16 Each is independently selected from hydrogen, C2-C30 alkyl, C2-C30 substituted alkyl, C2-C30 alkyl containing heteroatoms, or C2-C30 substituted alkyl containing heteroatoms, R 15 Selected from C2-C30 alkylene, C2-C30 substituted alkylene, C2-C30 heteroatom-containing alkylene, and C2-C30 heteroatom-containing substituted alkylene, p=0 or 1, two Rs 13 Whether the two R's are the same or different 14 Whether the two R's are the same or different 15 Whether the two R's are the same or different 16 Same or different, the two ps are the same or different.

8. The slowly expanding polymer microspheres according to claim 6, characterized in that, In equation (IV), R 13 R 14 R 16 Each is independently selected from hydrogen, C2-C20 alkyl, C2-C20 substituted alkyl, C2-C20 alkyl containing heteroatoms, or C2-C20 substituted alkyl containing heteroatoms, R 15 Selected from C2-C20 alkylene, C2-C20 substituted alkylene, C2-C20 heteroatom-containing alkylene, and C2-C20 heteroatom-containing substituted alkylene, p=0 or 1, two Rs 13 Whether the two R's are the same or different 14 Whether the two R's are the same or different 15 Whether the two R's are the same or different 16 Same or different, the two ps are the same or different.

9. The slowly expanding polymer microspheres according to claim 1, characterized in that, The stable crosslinking structural unit is formed by polymerization of a stable crosslinking agent, which contains at least two reactive groups selected from double bonds and / or aldehyde groups.

10. The slowly expanding polymer microspheres according to claim 9, characterized in that, The stabilizing crosslinking agent is selected from at least one of p-vinylbenzene, 1,4-pentadiene, N,N'-methylenebisacrylamide, N,N'-m-phenylenebismaleimide, formaldehyde, glyoxal, succinaldehyde, glutaraldehyde, adipaldehyde, o-phenylenedialdehyde, azelaic acid, octanedialdehyde, paraformaldehyde, and phenolic prepolymers.

11. The slowly expanding polymer microspheres according to any one of claims 1 to 10, characterized in that, Based on a total weight of 100 wt% for the acrylamide structural unit, anionic monomer structural unit, and cationic monomer structural unit, the amount of the crosslinking structural unit is 0.01 wt% to 0.5 wt%; and / or, Based on 100wt% of the crosslinked structural unit, the degradable crosslinked structural unit is 20-90wt%; and the stable crosslinked structural unit is 10-80wt%.

12. The slowly expanding polymer microspheres according to claim 11, characterized in that, Based on a total weight of 100 wt% for the acrylamide structural unit, anionic monomer structural unit, and cationic monomer structural unit, the amount of the crosslinking structural unit is 0.05 wt% to 0.5 wt%; and / or, Based on 100wt% of the crosslinked structural unit, the degradable crosslinked structural unit is 30~80wt%; and the stable crosslinked structural unit is 20~70wt%.

13. A slow-swelling polymer microsphere emulsion comprising a dispersed phase and the slow-swelling polymer microspheres as described in any one of claims 1 to 12.

14. The slow-swelling polymer microsphere emulsion according to claim 13, characterized in that, The dispersed phase includes an aqueous phase and / or an oil phase.

15. The slow-swelling polymer microsphere emulsion according to claim 14, characterized in that, The oil phase is selected from oil-soluble solvents.

16. The slow-swelling polymer microsphere emulsion according to claim 15, characterized in that, The oil phase is selected from at least one of hydrocarbon solvents and ester solvents.

17. The slow-swelling polymer microsphere emulsion according to claim 16, characterized in that, The hydrocarbon solvent is selected from at least one of aliphatic hydrocarbons, aromatic hydrocarbons, and petroleum fractions, and / or the ester solvent is selected from at least one of carboxylic acid esters and vegetable oils.

18. A method for preparing a slow-swelling polymer microsphere emulsion, used to prepare the slow-swelling polymer microsphere emulsion according to any one of claims 13 to 17, the preparation method comprising: The slow-swelling polymer microsphere emulsion is obtained by emulsion polymerization using components including acrylamide monomers, anionic monomers, cationic monomers, and crosslinking agents as raw materials, wherein the crosslinking agent includes degradable crosslinking agents and stable crosslinking agents; The anionic monomer is selected from at least one of the compounds shown in formula (ii): Formula (ii) In equation (ii), R5 is selected from -(CONH). n -R 2 -COOM or -(CONH) n -R 2 -SO3M, n is 0 or 1, R 2 Selected from hydrogen, alkyl, substituted alkyl, aromatic or substituted aromatic groups, M is selected from hydrogen, alkali metal or NH4. + R6, R7, and R8 are each independently selected from hydrogen, alkyl, or substituted alkyl groups; The cationic monomer is selected from at least one of the compounds shown in formula (iii): Equation (iii) In equation (iii), R9 is selected from -R 3 -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X or -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X,R 3 R 4 Each is independently selected from alkylene, substituted alkylene, or arylene, R 5 R 6 R 7 Each is independently selected from alkyl, substituted alkyl, aryl, or substituted aryl, m=0 or 1, X is selected from anion, R 10 R 11 R 12 Each is independently selected from hydrogen, alkyl, or substituted alkyl; The amount of acrylamide monomer is 100 parts, the amount of anionic monomer is 0-50 parts, the amount of cationic monomer is 0-50 parts, and the amount of water is 80-150 parts. The weight of anionic monomer and cationic monomer is not taken as 0. The biodegradable crosslinking agent contains a fluorescent group, an ester group, and at least two polymerizable double bonds.

19. The preparation method according to claim 18, characterized in that, The acrylamide monomer is selected from at least one of the compounds shown in formula (i): Equation (i) In equation (i), R1 is selected from -CONH2 or -R 1 -CONH2, R 1 R2, R3, and R4 are each independently selected from hydrogen, alkyl, or substituted alkyl.

20. The preparation method according to claim 19, characterized in that, In equation (i), R1 is selected from -CONH2 or -R 1 -CONH2, R 1 R2, R3, and R4 are each independently selected from hydrogen, C1-C10 alkyl, C1-C10 substituted alkyl, C6-C10 aryl, or C6-C10 substituted aryl, and R4 are each independently selected from hydrogen, C1-C10 alkyl, or C1-C10 substituted alkyl; and / or, In equation (ii), R5 is selected from -(CONH). n -R 2 -COOM or -(CONH) n -R 2 -SO3M, n is 0 or 1, R 2 Selected from hydrogen, C1-C10 alkyl, C1-C10 substituted alkyl, C6-C10 aryl, or C6-C10 substituted aryl, M is selected from hydrogen, alkali metal, or NH4. + R6, R7, and R8 are each independently selected from hydrogen, C1-C10 alkyl groups, or C1-C10 substituted alkyl groups; and / or, In equation (iii), R9 is selected from -R 3 -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X or -(CONH) m -R 4 -N(R 5 R 6 R 7 )·X,R 3 R 4 Each is independently selected from C1-C10 alkylene, C1-C10 substituted alkylene, C6-C10 arylene, or C6-C10 substituted arylene, R 5 R 6 R 7 Each is independently selected from C1-C10 alkyl, C1-C10 substituted alkyl, C6-C10 aryl, or C6-C10 substituted aryl, m=0 or 1, X is selected from halide ions, R 10 R 11 R 12 Each is independently selected from hydrogen, C1-C10 alkyl groups, or C1-C10 substituted alkyl groups.

21. The preparation method according to claim 18, characterized in that, By weight, the amount of acrylamide monomer is 100 parts, the amount of anionic monomer is 0-30 parts, the amount of cationic monomer is 5-30 parts, and the amount of water is 90-120 parts. The weight of anionic monomer is not taken as 0.

22. The preparation method according to claim 18, characterized in that, The fluorescent group is a fluorescein group.

23. The preparation method according to claim 18, characterized in that, The degradable crosslinking agent is selected from at least one of the compounds shown in formula (iv) or derivatives thereof: Formula (iv); In equation (iv), R 13 R 14 R 16 Each is independently selected from hydrogen, alkyl, substituted alkyl, heteroatom-containing alkyl, or heteroatom-containing substituted alkyl, R 15 Selected from alkylene, substituted alkylene, heteroatom-containing alkylene, or heteroatom-containing substituted alkylene, p=0 or 1, two Rs 13 Whether the two R's are the same or different 14 Whether the two R's are the same or different 15 Whether the two R's are the same or different 16 The two p's may be the same or different; the alkylene group may be a straight-chain alkylene group or a branched alkylene group.

24. The preparation method according to claim 23, characterized in that, In equation (iv), R 13 R 14 R 16 Each is independently selected from hydrogen, C2-C30 alkyl, C2-C30 substituted alkyl, C2-C30 alkyl containing heteroatoms, or C2-C30 substituted alkyl containing heteroatoms, R 15 Selected from C2-C30 alkylene, C2-C30 substituted alkylene, C2-C30 heteroatom-containing alkylene, and C2-C30 heteroatom-containing substituted alkylene, p=0 or 1, two Rs 13 Whether the two R's are the same or different 14 Whether the two R's are the same or different 15 Whether the two R's are the same or different 16 Same or different, the two ps are the same or different.

25. The preparation method according to claim 18, characterized in that, The stabilizing crosslinking agent contains at least two reactive groups, which are selected from double bonds and / or aldehyde groups.

26. The preparation method according to claim 18, characterized in that, The stabilizing crosslinking agent is selected from at least one of p-vinylbenzene, 1,4-pentadiene, N,N'-methylenebisacrylamide, N,N'-m-phenylenebismaleimide, formaldehyde, glyoxal, succinaldehyde, glutaraldehyde, adipaldehyde, o-phenylenedialdehyde, azelaic acid, octanedialdehyde, paraformaldehyde, and phenolic prepolymers.

27. The preparation method according to claim 18, characterized in that, Based on a total weight of 100 wt% for the acrylamide monomers, anionic monomers, and cationic monomers, the amount of the crosslinking agent is 0.01 wt% to 0.5 wt%; and / or, Based on a total crosslinking agent content of 100 wt%, the amount of the degradable crosslinking agent is 20-90 wt%, and the amount of the stable crosslinking agent is 10-80 wt%.

28. The preparation method according to claim 18, characterized in that, Based on a total weight of 100 wt% for the acrylamide monomers, anionic monomers, and cationic monomers, the amount of the crosslinking agent is 0.05 wt% to 0.5 wt%; and / or, Based on 100wt% of the crosslinking structural unit, the amount of the degradable crosslinking agent is 30~80wt%, and the amount of the stable crosslinking structural unit is 20~70wt%.

29. The preparation method according to any one of claims 18 to 28, characterized in that, The preparation method includes: (1) mixing raw material I, including the acrylamide monomer, the anionic monomer, the cationic monomer, the crosslinking agent, and water, to form an aqueous phase; mixing raw material II, including the emulsifier and the oil-soluble solvent, to form an oil phase; and mixing the initiator with water to obtain an initiator solution; (2) emulsifying the aqueous phase and the oil phase to obtain an emulsion mixture; and (3) adding the initiator solution to the emulsion mixture to polymerize and obtain the slow-swelling polymer microsphere emulsion.

30. The preparation method according to claim 29, characterized in that, The pH value of the aqueous phase is 7-11; and / or, The emulsifier is a single emulsifier or a mixture of multiple emulsifiers with different HLB values, wherein the HLB value of the single emulsifier or the mixture of emulsifiers is 5 to 9.

31. The preparation method according to claim 30, characterized in that, The emulsifier is selected from at least one of fatty alcohols, alkylphenols, fatty acids, fatty acid esters, alkoxy adducts of amines, and partially hydroxylated or esterified products of polyols.

32. A method for preparing slow-expanding polymer microspheres, used to prepare the slow-expanding polymer microspheres according to any one of claims 1 to 12, the preparation method comprising: (A) Disperse the slow-swelling polymer microsphere emulsion according to any one of claims 13 to 17 or the slow-swelling polymer microsphere emulsion obtained by the preparation method according to any one of claims 18 to 31 in an alcohol solvent, stir thoroughly, and then filter to remove solid I; (B) Disperse solid I again in an alcohol solvent, stir thoroughly, and then filter to remove solid II; (C) Dry solid II to obtain the slow-swelling polymer microspheres.

33. The preparation method according to claim 32, characterized in that, The alcohol solvent is selected from methanol and / or ethanol.

34. The preparation method according to claim 33, characterized in that, The slow-swelling polymer microsphere emulsion is added dropwise to the alcohol solvent.

35. The application of the slow-expanding polymer microspheres according to any one of claims 1 to 12, the slow-expanding polymer microsphere emulsion according to any one of claims 13 to 17, the slow-expanding polymer microsphere emulsion obtained by the preparation method according to any one of claims 18 to 31, or the slow-expanding polymer microspheres obtained by the preparation method according to any one of claims 32 to 34 in the field of oilfield development.

Citation Information

Patent Citations

  • Volume-expansion granular profile control agent for oil recovery

    CN104371679A

  • Pre-crosslinking swell particle profile-control agent and preparation method thereof

    CN105368422A

  • Temperature-resistant and salt-resistant multi-component copolymerization pre-crosslinked gel particle and preparation method and application thereof

    CN112279963A

  • Polymer microsphere with controllable expansion time and preparation method thereof

    CN109608577A

  • Multi-network type monodispersed polyacrylamide-based polymer gel microsphere and preparation method thereof

    CN109666469A